Antioxidant Activity and Cytotoxicity of Baru Nut Oil (Dipteryx alata Vogel) Nanoemulsion in Human Cells - José Queiroz; Arthur Figueredo; Bruno Silva Sá; Daniel Carneiro Moreira; João Bueno Nunes; Peter Eaton; José Roberto Souza de Almeida Leite; Andreanne Gomes Vasconcelos (Applied Nano)
Baru nut oil (Dipteryx alata Vogel) is a lipidic extract from a species endemic to the Cerrado biome, renowned for its antioxidant potential. This study aimed to develop a nanoemulsion containing baru nut oil (BNON) using lecithin and polysorbate 80, and to evaluate its antioxidant activity and cytotoxicity. The physicochemical properties of BNON were characterized, and its cytotoxicity was assessed in human erythrocytes and keratinocytes. Antioxidant activity was evaluated using the DPPH method and inhibition of AAPH-induced hemolysis. BNON exhibited a droplet size of 530.1 ± 20.48 nm, a polydispersity index of 0.496 ± 0.057, and a zeta potential of −35.7 ± 2.19 mV. Free baru nut oil showed no cytotoxicity to keratinocytes or erythrocytes within the concentration ranges tested (1.0–0.031 mg/mL and 0.8–0.006 mg/mL, respectively). In contrast, BNON displayed cytotoxic effects on keratinocytes and erythrocytes only at the highest tested concentration. Atomic force microscopy analysis of erythrocytes from the hemolysis assay revealed normal morphology for cells treated with free oil at 0.8 mg/mL, whereas cells treated with BNON at the same concentration exhibited a slightly widened concave center. Free oil at 0.8 mg/mL significantly protected erythrocytes from AAPH-induced hemolysis, while BNON did not. However, BNON (5 mg/mL) demonstrated free radical scavenging activity, quantified at 0.0074 mg Trolox equivalents/mg via the DPPH assay. These findings suggest that baru nut oil has potential as an antioxidant product, although further optimization of the nanoformulation is required.